Assessing the Cost Structure, Income, and Efficiency of Red Chili Farming in Kayu Aro District, Kerinci Regency, and Implications for Rural Government Policies - Ulma, Riri Oktari; Damayanti, Yusma; Elwamendri, Elwamendri; Asropi, Asropi; Effran, Endy (Jurnal AGRISEP, 2023)
This research aims to describe a general overview of red chili farming in Kayu Aro Sub-district and Kerinci Regency generally, analyze the cost structure and income and the feasibility of red chili farming, and to analysis implementation to rural goverment. This research was conducted in Kayu Aro Sub-district, specifically in Batang Sangir and Sungai Tanduk villages. The number sampled in this study was 54 farmers. Both primary and secondary data were utilized. The data analysis methods used were descriptive analysis and quantitative analysis. The research shows that red chili farming in the research area is a traditional practice that has been passed down through generations and remains deeply rooted in the culture. Consequently, all basic farming activities are based on traditional experiences. The first step in red chili farming is seed preparation, where farmers use local seeds known as LOKER (Local Kerinci), obtained from previous harvests, eliminating the need to purchase seeds. Generally, red chili farmers in the research location have small land holdings where they own on average 0.18 hectares. The red chili farming maintenance activities include transplanting, staking, weeding, fertilization, as well as pest and disease control.  The cost structure consists of fixed costs amounting to IDR 1,413,000/MT/year and variable costs amounting to IDR 27,985,000/MT/year. The income obtained from red chili farming is IDR 18,963,400/farmer/MT. The R/C ratio for red chili farming is 1.70, indicating that the farming activity in the research area is profitable and viable to pursue.